DENTAL CHARACTERISTICS OF PATIENTS SUFFERING FROM TEMPOROMANDIBULAR DISORDERS - Kamal, Adeel Tahir; Fida, Mubassar; Sukhia, Rashna H (Journal of Ayub Medical College Abbottabad, 2020)
Background: The role of malocclusion in the aetiology of TMDs has been discussed extensively in literature, however, the varied results from different studies have made it difficult to reach a consensus. The objective of this study was to determine the association of dental characteristics and temporomandibular disorders (TMDs). Method: This case-control study involved a total of 266 patients who were equally divided into 2 groups (TMD/Non-TMD) based on the score obtained from the Fonseca’s questionnaire. Dental characteristics such as class of malocclusion, overjet, overbite, crossbite, and crowding were assessed. The Chi-square test was used to determine an association between each dental characteristic and TMD. Odds ratios were calculated using simple and multiple logistic regression. Results: Significant associations were found between crowding, crossbites, and molar relationships in males. Simple logistic regression showed significant associations for class II malocclusion (OR=0.56, p=0.024) and crowding (OR=0.35, p<0.001) with TMD. Multiple logistic regression showed significant associations for crowding (p<0.001) and class III malocclusion (p=0.002). Conclusion: Male patients with dental characteristics such as improper molar relationships, crossbites, and crowding should seek orthodontic treatment to prevent the onset of TMDs. Higher odds of TMD were found in patients with Angle’s class III malocclusion. Keywords: Temporomandibular Joint Disorders; Malocclusion; Crowding